The Challenging Diagnosis of Primordial Odontogenic Tumor - Lucas Novaes Teixeira; Cristiane Furuse; Fabrício Passador Santos; Andresa Borges Soares; Eder Magno Ferreira de Oliveira; Ney Soares de Araújo; Vera Cavalcanti de Araújo (Case Reports in Dentistry)
Primordial odontogenic tumor (POT) is a benign mixed odontogenic tumor comprised of a loose connective tissue with a similar morphology with dental papilla and exhibiting in its periphery the presence of a columnar epithelium. POT occurs in young patients and typically is associated with an unerupted tooth, with the mandible being the main anatomic site of occurrence. The present manuscript is aimed at describing a new case of POT and reviewing the main biologic findings related to this odontogenic tumor.